Manifestating the Sub-District of Sri Padang Resilent Disaster Focuses on the Village Resilience Assessment Component in 2022 - Sipayung, Antonio; A.S.P, Mehaga; A.K, Manoarfa; T.A.N, Halawa; N.U, Aini; M, Arja; A.S, Manik; A.R, Pasaribu; M.H, Ginting; R, Oktaviany; E.R, Nasution; R.A, Inaya (Talenta Publisher, 2023)
Flooding, stunting, and limited land are problems that routinely occur in the village of Sri Padang, Sub-district Rambutan, City of Tebing Tinggi. The flooding that occurs is a shipment from areas in the highlands through large rivers (from upstream to downstream). The flooding that occurred was also the result of a poor drainage system in the Sri Padang area. Stunting problems that occur in Sri Padang Village have recorded 20-30 cases. Society still thinks that stunting cases are due to hereditary (genetic) factors, not due to lack of nutritional intake since the growth of toddlers. Limited land in Sri Padang Village is because some areas are on the railway line, making it difficult to be used as a farming area or building a septic tank site.